155 'An integral part of treatment': What oncologists think about early integration of palliative care into oncology clinics. (14th March 2023) - Kano, Y; Want, J; Elliot, K; Stevens, AM; Droney, J; Kamal, L; Halley, A; Wood, J; Tweddle, A
Abstract : Background: The Integrated Symptom Control and Palliative Care 'Triggers' service was developed to support oncology outpatients to live as well as possible throughout their cancer journey. The aim of this survey was to evaluate the views of oncology clinicians about the 'Triggers' service in a tertiary referral oncology centre 6 years after the service was initially established. Methods: A brief anonymous staff feedback questionnaire was developed with PPI input comprised of four questions with structured answers and one free text question. The survey was carried out in 2018 and repeated in 2022. All oncology staff working in clinics where the 'Triggers' service was invited to participate. Descriptive analysis was carried out on the structured questions and thematic analysis on the free text question. This service evaluation was approved by the local Committee for Clinical Research. Result: Feedback forms were received from 42 staff members in 2018 and 52 in 2022. 49/52 (94%) rated the value of the service for patients and families as very positive. (69% in 2018). 50/52 (96%) thought the service had a very positive impact on patients. (69% in 2018). 96% (50/52) felt it had a positive effect on the running of the clinic. (76% in 2018). Three strong themes were identified from the 2022 free text responses. The 'Triggers' service provides urgent and prompt access to the palliative care team for management of patients with complex needs. The oncology teams felt that the 'Triggers' service was helpful to the clinics and staff working in them. Finally, they recognised that the 'Triggers' service is integrated and routinised into the oncology clinics. Conclusions: As the 'Triggers' early palliative care service has become embedded and integrated into the oncology outpatient clinics over time, oncology clinicians have become increasingly aware of the associated benefits for patients and staff.